Hubungan Dukungan Manajemen Rumah Sakit dan Sikap Kepala Ruangan dengan Kepatuhan Perawat - Wardani, JESSIKA PRAMUDYA; GUNTUR A. GAMA MUHAMMAD; DIANSANTO PRAYOGA (Hang Tuah Medical Journal, 2024)
The importance of implementing safety measures and improving service quality in hospitals is supported by nurses' compliance in preventing patient fall risks. The factors of management support and inpatient chief support are also considered to influence nurses' compliance in following SOP to prevent patient fall risks at RSUD Blambangan. This study is to determine the correlation between hospital management support and inpatient chief support with nurses' compliance in implementing the SPO for preventing patient fall risks at RSUD Blambangan. This research is a quantitative study. The sample of this research are 103 nurses. The results of that correlation between inpatient chief attitude and nurses' compliance showed no significant correlation, with p-value of 0.126. Meanwhile, the relationship between hospital management support and nurses' compliance in implementation of patient fall risk prevention in the inpatient ward showed a significant relationship, with p-value of 0.007. The analysis of correlation test results indicates that the inpatient chief attitude variable is not related. On the other hand, the hospital management support variable has a significant correlation with nurses' compliance in implementing SPO for preventing patient fall risks in the inpatient ward of RSUD Blambangan.